Empire of pain the secret history of the Sackler dynasty - Keefe, Patrick Radden 1976- (Doubleday, 2021)
"The highly anticipated portrait of three generations of the Sackler family, by the prize-winning, bestselling author of SAY NOTHING The Sackler name adorns the walls of many storied institutions: Harvard, the Metropolitan Museum of Art, Oxford, the Louvre. They are one of the richest families in the world, known for their lavish donations to the arts and sciences. The source of the family fortune was vague, however, until it emerged that the Sackler's were responsible for making and marketing Oxycontin, a blockbuster painkiller that was a catalyst for the opioid crisis. Empire of Pain is a masterpiece of narrative reporting and writing, exhaustively documented and ferociously compelling"--
Includes bibliographical references (pages 446-515) and index
Keywords: Sackler, Arthur M. -- 1913-1987; Sackler, Arthur M. / 1913-1987 / (DE-588)119327015 / (DE-627)080135935 / (DE-576)212125427; Sackler family; Sackler, Arthur M / Family; Purdue Pharma L.P / History; Pharmaindustrie / (DE-627)091383137 / (DE-2867)13002-3; Opiate / (DE-627)656552573 / (DE-2867)28894-0; Unternehmensgeschichte / (DE-627)091360099 / (DE-2867)12046-2; USA / (DE-627)091396867 / (DE-2867)17829-1; Rich people / United States / Biography; Pharmaceutical industry / Marketing; Pharmaceutical industry / Corrupt practices